Phytochemical screening and cytotoxic evaluation of Bauhinia scandens leaf extracts using HeLa and T47D cell lines - Lianah Lianah; RITA ARIYANA NUR KHASANAH; DWIMEI AYUDEWANDARI PRANATAMI; KRISANTINI KRISANTINI (Society for Indonesian Biodiversity, 2021)
Abstract. Lianah L, Khasanah RAN, Pranatami DA, Krisantini K. 2021. Phytochemical screening and cytotoxic evaluation of Bauhinia scandens leaf extracts using HeLa and T47D cell lines. Biodiversitas 22: 913-919. The aim of the study was to analyze the phytochemical contents and todetermine the cytotoxic activities of Bauhinia scandens leaf ethanol extracts against HeLa (human cervical cancer) and T47D (breast cancer) cell culture lines. Using a standard protocol, it was found that leaf extract of B. scandens contains phytochemicals that are widely known to have medicinal properties, such as phenols (17.57±0.098% w/w), flavonoids (5.91±0.098% w/w), saponins (19.42±0.091% w/w), tannins (1.24±0.035% w/w), alkaloids (1.31±0.001% w/w) and steroids (0.08±0.007% w/w). Results of 24-hr Microculture Tetrazolium Salt (MTT) assay show that leaf extracts of B. scandens can suppress cell growth at a half-maximal inhibitory concentration (IC50) of 1.95 ?g/mLfor HeLa cells and 4.54?g/mL for T47D cells. This indicates that B. scandens is a potentially strong candidate for anti-cancer agents. The cytotoxic activities of the leaf extracts of B. scandens can be attributed to the total effects of the phytochemical compounds found. Further studies are recommended in order to isolate and determine individual effects of bioactive compounds in B. scandens.